Age-Adjusted Normative Values for Hip Patient-Reported Outcome Measures. Issue 1 (January 2022) - Sharfman, Zachary T.; Safran, Nathan; Amar, Eyal; Varshneya, Kunal; Safran, Marc R.; Rath, Ehud
Background: Patient-reported outcome measures (PROMs) are essential clinical instruments used for assessing patient function, assisting in clinical decision making, and quantifying outcomes of surgical and nonsurgical management. However, PROMs are often designed using patients with preexisting pathology and typically assume that a patient without the pathology would have a perfect or near perfect score. This may result in unrealistic expectations or falsely underestimate how well a patient is doing after treatment. The influence of age on PROMs about the hip of healthy individuals has not been studied. Hypothesis: We hypothesize that in asymptomatic individuals hip-specific PROM scores will decrease in an age-dependent manor. Study Design: Cross-sectional study; Level of evidence, 3. Methods: In this multicenter survey study, volunteers who denied preexisting hip pathology and previous hip surgery completed 3 PROMs online or as traditional paper questionnaires. The International Hip Outcome Tool (iHOT), the modified Harris Hip Score (mHHS), and the Hip Outcome Score–Activities of Daily Living (HOS-ADL) and HOS—Sport were completed. Analysis of variance with a Tukey post hoc test was used to analyze differences in PROMs among subgroups. An independent-samples Student t test and a χ 2 test were used to analyze differences in continuous and categorical data, respectively. Results: In total 496, 571, 534, and 532 responses were collected for the iHOT, mHHS, HOS-ADL, and HOS–Sport, respectively. Respondents' PROMs were scored and arranged into 3 groups by age: <40 years, 40 to 60 years, and >60 years. The iHOT, mHHS, HOS-ADL, and HOS–Sport of these asymptomatic respondents all decreased in an age-dependent manner: iHOT (<40, 94.1; 40-60, 92.4; >60, 87.0), mHHS (<40, 94.8; 40-60, 91.3; >60, 89.1), HOS-ADL (<40, 98.4; 40-60, 95.0; >60, 90.9), and HOS–Sport (<40, 95.7; 40-60, 82.9; >60, 72.9) (analysis of variance between-group differences, P < .05). Conclusion: This study demonstrated that the iHOT, mHHS, and HOS-ADL and HOS–Sport scores in asymptomatic people decrease in an age-dependent manner. It is important to compare a patient's outcome scores with the age-normalized scores to establish an accurate reference frame with which to interpret outcomes.